The Effect of Using Spelling Bee Games Toward Students’ Vocabulary Mastery - Tiara Agustina; Kurnia Budiyanti (Universitas Negeri Medan, 2024)
Vocabulary is very important for English language skills, and improving it is a challenge. Spelling bee games, an engineering-based learning tool, can help students become more proficient with vocabulary. This study aims to determine significant differences in vocabulary mastery among grade 8 students at SMPN 23 Pekanbaru. The research was conducted using the pre-experimental one group pre-test post-test method, with a sample size of 36 students, while for sample selection the researcher used a purposive sampling technique. In collecting data, researchers used multiple choice questions. The results showed that there was a significant difference in vocabulary mastery and the researcher used a paired sample T test using the SPSS version 23 with a significance value of 0.000, lower than the threshold of 0.05. In conclusion, spelling bee games can be an appropriate technique to improve vocabulary skills among students.